Following kinetics and dynamics of DGEBA-aniline polymerization in nanoporous native alumina oxide membranes – FTIR and dielectric studies. (26th June 2015) - Tarnacka, Magdalena; Dulski, Mateusz; Starzonek, Szymon; Adrjanowicz, Karolina; Mapesa, Emmanuel U.; Kaminski, Kamil; Paluch, Marian
Abstract: Fourier Transform Infrared and Broadband Dielectric Spectroscopies were applied to follow kinetics as well as molecular dynamics upon step-growth polymerization of bisphenol-A diglycidyl ether (DGEBA) with aniline both in bulk and in anodic aluminum oxide (AAO) membranes. For the first time the dynamics and kinetics of a curing epoxy system under confinement were analyzed and compared with the reaction in the bulk. As it turned out, polymerization is faster under confinement, compared to the analogous reaction carried out in the bulk system at the same temperature conditions. Additionally, the reaction speeds up with the degree of confinement. Furthermore, it was found that the initial step of the polymerization is significantly reduced or even suppressed in nanochannels; this is evident from the observation that kinetic curves do not follow sigmoidal shape that is characteristic for the autocatalytic type of chemical reactions. FTIR data showed unquestionably that the rate of reaction is slower at the surface of the pores with respect to the polymerization at the core of nanochannels. This finding is in tandem with Monte Carlo simulation reporting lower reactivity of the functional units close to the pore walls. Moreover, we found out that the activation barrier for the polymerization remains unchanged under confinement. Finally, dielectric measurements revealed that there is a characteristic change in the slope of segmental relaxation times plotted as a function of the time of reaction under confinement, a phenomenon whose comprehension demands further investigation. Graphical abstract: Highlights: The speed of reaction is enhanced in nanochannels. The initial step of reaction is reduced or even suppressed in nanochannels. The rate of reaction is different at the surface and the core of porous. A change in slope in segmental relaxation times plotted vs time is observed.